2010
DOI: 10.1111/j.1745-7599.2010.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

A literature review: Advance directives and patients with implantable cardioverter defibrillators

Abstract: Implementation of advanced directives in patients' medical care will need to be encouraged in the event of illness. Advanced practice nurses can provide clear explanations of patients' treatment choices in outpatient and inpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…and family well, 46,59,62 and who are well trained in ACP facilitation. 56,65 Literature in nursing homes highlighted that while patients and carers wanted health care professionals to initiate ACP discussions, they were concerned about whether the professionals had the capacity to engage in these discussions because of staff shortages.…”
Section: Initiation Of Acp Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and family well, 46,59,62 and who are well trained in ACP facilitation. 56,65 Literature in nursing homes highlighted that while patients and carers wanted health care professionals to initiate ACP discussions, they were concerned about whether the professionals had the capacity to engage in these discussions because of staff shortages.…”
Section: Initiation Of Acp Discussionmentioning
confidence: 99%
“…61,65 Some reviews showed that patients and carers recognized that ACP discussions may be recurring events rather than one-off exercises. This seemed to be particularly relevant in the context of heart disease, 44,59 where patients may wish to discuss their options at specific transitions in their care and revise their opinions on the use of implantable defibrillators. Other reviews that did not focus on a particular health condition also found preferences for recurring ACP discussion.…”
Section: Timing Of Acp Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Completion rates for ADs increased when information was given to participants in advance of their admission [3]. This literature review has tried to demonstrate different kinds of patient education in increasing ADs completion rates.…”
Section: Resultsmentioning
confidence: 99%
“…Advance directives (ADs) were formal statement made by a person about how he wants medical decisions for himself made and who should make these decisions when he can no longer make such decisions for himself [8]. There are two kinds of ADs: living will (LW) which is a treatment directive, and appointment directive that is durable power of attorney for health care (DPHAC) [3]. ICGH Conference Proceedings…”
Section: Introductionmentioning
confidence: 99%